The The Effect of Locus of Control and Peer Pressure on the Ethical Behavior of Students: A Case Study at STIE Sutaatmadja - Andin Diagi; Pipit Atinah (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2025)
This study aims to determine: (1) the effect of Locus of Control on students’ ethical behavior, (2) the effect of Peer Pressure on students’ ethical behavior, and (3) the simultaneous effect of Locus of Control and Peer Pressure on students’ ethical behavior. This research uses a quantitative approach with data collection techniques through questionnaires distributed to 54 active students of STIE Sutaatmadja. Sampling was carried out using purposive sampling technique. The independent variables in this study are Locus of Control (X1) and Peer Pressure (X2), while the dependent variable is Students’ Ethical Behavior (Y). Classical assumption tests used in this study include normality test, heteroscedasticity test, and multicollinearity test. Meanwhile, the hypothesis testing includes t-test, F-test, and multiple linear regression analysis. The results of the study show that the Locus of Control variable has a positive and significant effect on students' ethical behavior. This is evidenced by a significance value of 0.000 < 0.05 and a t-count of 8.954 > t-table of 2.007, thus the first hypothesis (H1) is accepted. Meanwhile, the Peer Pressure variable does not have a significant effect on students’ ethical behavior, as shown by a significance value of 0.279 > 0.05 and a t-count of -1.095 < t-table of 2.007. Therefore, the second hypothesis (H2) is rejected. However, simultaneously, both variables (Locus of Control and Peer Pressure) have a significant effect on students’ ethical behavior, with a significance value of 0.000 < 0.05 and an F-count of 41.445 > F-table of 3.18, indicating that the third hypothesis (H3) is accepted. The regression equation obtained is: Y = 12.747 + 0.811X1 – 0.099X2, and the Adjusted R² value is 0.604, indicating that 60.4% of students’ ethical behavior can be explained by the two independent variables. These findings indicate that internal factors are more dominant in shaping students’ ethical behavior compared to external influences such as peer pressure.